MURAL SEBAGAI MEDIA PENGENALAN OLAHRAGA TRADISIONAL BALI DI LAPANGAN ASTAGINA PADANGSAMBIAN KELOD DENPASAR - Putu Astri Lestari; A.A. Sagung Intan Pradnyanita; Made Arini Hanindharputri (LPPM Institut Desain dan Bisnis Bali, 2020)
This community service activity was carried out by a team of lecturers from the Bali Design and Business Institute (IDB Bali) together with the Visual Communication Design Department Student Association and also the “Perkamen” Student Activity Unit held at the end of 2020 to be precise starting on November 7, 2020 until handover on 13. December 2020, at the Astagina Field, Padangsambian Klod Village, West Denpasar. This activity received a very good welcome and high enthusiasm from both lecturers, students and also the community in the area, and received sponsorship from Dulux. The purpose of the collaborative mural activity between IDB Bali and Padangsambian Klod Village and sponsored by PT ICI Paints Indonesia or better known as Dulux ™ premium paint manufacturer apart from being a forum for pouring out student talents in the field of images in the realm of developing modern designs in society, as well as a medium in introducing Balinese traditional sports culture to the general public. Some of the supporting factors for these activities include: the enthusiasm of lecturers and students in mural activities, sponsorship support from Dulux in supporting the paint used for murals, and the support of the Padangsambian Klod Village. Some of the obstacles faced during this mural activity include: (1) Erratic weather, especially rain, (2) The Covid 19 outbreak caused the team involved in the work to not work optimally to avoid the crowd.